Substitution of Tofu for Egg in Making Pound Cake - Ita Karnita; Surya Aditya Wahyono; Sofie Trisna Dwijaya (Universitas Pendidikan Indonesia, 2023)
The research objective of Substitution of Tofu for Egg in Making Pound Cake Bakery and cake shop business trends have increased significantly. Increased demand from customers for bakery and pastry products requires the bakery and cake shop industry to increase production to meet customer demand. However, there is a group of people who cannot enjoy pound cake because pound cake contains eggs as one of its basic ingredients so that those who are vegan and who have allergies to eggs cannot enjoy pound cake. Therefore, the author wishes to make a new innovation by substituting tofu for eggs so that pound cake can be enjoyed by those who are vegan or have allergies to eggs. The research method used is experimental. Data collection techniques used observation, literature study, panelis rating The answer to each instrument item that uses a Likert scale has gradations from very positive to very negative. The author conducted panelist tests on 10 professional panelists and 20 consumer panelists. The results of the assessment of the color aspect The results of the value of the color aspect, the experimental pound cake received 125. Assessment results from the aroma aspect The results of the value of the aroma aspect, the experimental pound cake received 124 points with an average value of 4.1. The results of the assessment of the taste aspect The results of the value of the taste aspect, the experimental pound cake received points of 118 with an average value of 3.9. The results of the assessment of the texture aspect The results of the value of the texture aspect, the experimental pound cake received points of 132 with an average value of 4.4.